MRI-based brain morphometry correlates of chronic pain in knee osteoarthritis - Alshuft, Hamza (2015)
Chronic pain is a complex experience that involves sensory, emotional, and cognitive aspects. The neurobiological mechanisms are therefore expected to be complex, widespread and largely maladaptive. Recent research of neuroimaging in chronic pain suggests cerebral re-organization on a structural level as a consequence of chronic pain. However, a combined and large-scale brain morphological profile in chronic pain to investigate its neural substrates has not been elucidated. The research presented aims to investigate morphological brain correlates and putatively related behavioural and cognitive aspects of chronic pain due to primary nociceptive knee osteoarthritic disorder using advanced imaging techniques for manual, voxel-based, and surface-based analysis, and questionnaire-based participants’ characterization.